Additive manufacturing of concrete in construction: potentials and challenges of 3D concrete printing. Issue 3 (2nd July 2016) - Bos, Freek; Wolfs, Rob; Ahmed, Zeeshan; Salet, Theo
ABSTRACT: Additive manufacturing is gaining ground in the construction industry. The potential to improve on current construction methods is significant. One of such methods being explored currently, both in academia and in construction practice, is the additive manufacturing of concrete (AMoC). Albeit a steadily growing number of researchers and private enterprises active in this field, AMoC is still in its infancy. Different variants in this family of manufacturing methods are being developed and improved continuously. Fundamental scientific understanding of the relations between design, material, process, and product is being explored. The collective body of work in that area is still very limited. After sketching the potential of AMoC for construction, this paper introduces the variants of AMoC under development around the globe and goes on to describe one of these in detail, the 3D Concrete Printing (3DCP) facility of the Eindhoven University of Technology. It is compared to other AMoC methods as well as to 3D printing in general. Subsequently, the paper will address the characteristics of 3DCP product geometry and structure, and discuss issues on parameter relations and experimental research. Finally, it will present the primary obstacles that stand between the potential of 3DCP and large-scale application in practice, and discuss the expected evolution of AMoC in general.